VIRTUE, HAPPINESS, AND EMOTION - Kauppinen, Antti (Les ateliers de l'éthique / The Ethics Forum, 2022)
Philosophers have tried very hard to show that we must be virtuous to be happy. But as long as we stick to the modern understanding of happiness as something experienced by a subject – and I argue against contemporary eudaimonists that we should indeed do so – there can at best exist a contingent causal connection between virtue and happiness. Nevertheless, we have good reason to think that being virtuous is non-accidentally conducive to happiness. Why? First, happiness is roughly the experiential condition of enjoying predominantly positive affective phenomenal states concerning things that are subjectively important to us. I argue that this straightforward sentimentalism about happiness has several advantages over Daniel Haybron’s emotional condition account. Second, insofar as we’re virtuous, we can correctly identify what is worth doing in our particular situation and will skillfully pursue it. At the same time, we’re not bothered by things that are not worth caring or worrying about. Consequently, virtuous people are likely to enjoy central positive emotions related to success and approval by others, and avoid common negative emotions related to social comparison or avarice. While their happiness is still in part a matter of luck, it is such to a lesser degree than for the rest of us.